Thermal and catalytic dehydrogenation of the guanidine-borane adducts H3B hppH (hppH = 1,3,4,6,7,8-hexahydro-2H-pyrimido(1,2-a)pyrimidine) and H3B N(H)C(NMe2)2: a combined experimental and quantum chemical study - Ciobanu, Oxana; Allouti, Fayçal; Roquette, Pascal; Leingang, Simone; Enders, Markus; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2008)
Herein thermal and catalytic dehydrogenation of the guanidine-borane adducts H3B·hppH (hppH = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidine) and H3B·N(H)C(NMe2)2 are analysed. Thermal decomposition of H3B·hppH at 80 °C leads to [HB(μ-hpp)]2 and a second boron hydride, which is tentatively identified as [(κ2N-hpp)BH2]. Decomposition in boiling toluene (110 °C) leads to a mixture of [H2B(μ-hpp)]2 and [HB(μ-hpp)]2, from which [H2B(μ-hpp)]2 can be separated and crystallised. In the presence of a catalyst (with Cp2TiCl2/nBuLi or [Rh(1,5-cod)Cl]2 as precatalysts) dehydrogenation at 80 °C leads predominantly to [H2B(μ-hpp)]2. In the case of H3B·N(H)C(NMe2)2 uncatalysed dehydrogenation turns out to be a very slow process even at 110 °C. Interestingly, the ultimate product of this process is oligomeric methylimino borane, [HBNMe]n. This pathway can be modelled and understood with the aid of quantum chemical calculations. Faster dehydrogenation can be initiated by addition of a catalyst. Finally, the possible mechanisms for thermal and Cp2Ti-catalysed dehydrogenation are analysed for the model compound H3B·N(H)C(NH2)2 by means of quantum chemical (DFT) calculations.(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)
Die Buchstaben "H" und "a" im Ausdruck "2H-pyrimido[1,2-a]" sind kursiv dargestellt
Im Titel ist die Zahl "3" im Ausdruck "H3B hppH" und "H3B N(H)C(NMe2)2" sowie die Zahl "2" im Ausdruck "H3B N(H)C(NMe2)2"tiefgestellt
First published: 28 November 2008
Gesehen am 01.12.2022